2007
DOI: 10.4067/s0717-77122007000200005
|View full text |Cite
|
Sign up to set email alerts
|

Anisakidae parasitos de congro-rosa, Genypterus brasiliensis Regan, 1903 comercializados no estado do Rio de Janeiro, Brasil de interesse na saúde pública

Abstract: ) were parasitized by live larvae of Anisakidae. The collected species were represented by Anisakis physeteris, Anisakis simplex, Anisakis sp., Pseudoterranova decipiens, Pseudoterranova sp., Hysterothylacium sp., Raphidascaris sp., Contracaecum sp. and Terranova sp. The species Anisakis sp. and A. simplex presented the higher prevalences, both with 13,5% whereas A. physeteris presented the lower prevalence 1,35%. The other species, Pseudoterranova sp., P. decipiens, Hysterothylacium sp., Raphidascaris sp., Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 5 publications
0
13
0
7
Order By: Relevance
“…High prevalence (97.5%) was also reported in Prionotus punctatus (Bloch, 1793) from the municipality of Angra dos Reis, state of Rio de Janeiro (Bicudo et al, 2005) and the mean intensity and abundance were higher than those observed in this study. Conversely, Knoff et al (2007) have related 27% prevalence of anisakids Anisakis sp., A. physeteris Baylis, 1923, A. simplex (Rudolphi, 1809, Pseudoterranova sp., P. decipiens (Krabbe, 1878), Hysterothylacium sp., Raphidascaris sp., Contracaecum sp. and Terranova sp.…”
Section: Discussionmentioning
confidence: 99%
“…High prevalence (97.5%) was also reported in Prionotus punctatus (Bloch, 1793) from the municipality of Angra dos Reis, state of Rio de Janeiro (Bicudo et al, 2005) and the mean intensity and abundance were higher than those observed in this study. Conversely, Knoff et al (2007) have related 27% prevalence of anisakids Anisakis sp., A. physeteris Baylis, 1923, A. simplex (Rudolphi, 1809, Pseudoterranova sp., P. decipiens (Krabbe, 1878), Hysterothylacium sp., Raphidascaris sp., Contracaecum sp. and Terranova sp.…”
Section: Discussionmentioning
confidence: 99%
“…Human infections by anisakids are not common in Brazil. However, several authors have reported the presence of these parasites in marine fish, generally in greater prevalences in comparison with other helminths (São Clemente et al, 1994;Luque, 2004;Knoff et al, 2007Knoff et al, , 2013Barros, 2012). Anisakid larvae have been reported by several authors in species of fish of economic importance such as: Anchoa tricolor, Netuma barba, Brevoortia aurea, Pagrus pagrus, Prionotus punctatus, Genypterus brasiliensis, Aluterus monoceros, Paralichthysis isoceles, Rhamdia quellen, Lophius gastrophysus, Lutjanus analis, Sardinella brasiliensis, and Selene setapinnis (Palm, 1997;São Clemente et al, 1994;Cordeiro and Luque, 2004;Bicudo et al, 2005;Knoff et al, 2007;Saad and Luque, 2009;Dias et al, 2010;Felizardo et al, 2009;La Rue et al, 2010;Saad et al, 2012;Knoff et al, 2013;Hermida et al, 2014;Moreira et al, 2015;Fontenelle et al, 2015).…”
Section: Introductionmentioning
confidence: 98%
“…A presença de larvas na musculatura, certamente, aumenta o potencial zoonótico desses parasitos que podem infectar o homem via ingestão de carne de peixe crua ou insuficientemente cozida (ACHA; SZYFRES, 2003). Recentemente, relatos de Knoff et al (2004Knoff et al ( , 2007) mencionaram a presença de anisaquídeos na musculatura de um peixe marinho (Genypterus brasiliensis) no Brasil, chamando ainda mais a atenção para o potencial zoonótico dessas larvas por causa da sua localização no peixe.…”
Section: Introductionunclassified
“…Entretanto, São Clemente et al (1994) observaram em pargos infectados com anisaquídeos que, após 2 horas de exposição à temperatura de -2,9 °C, todas as larvas coletadas encontravam-se mortas, embora seja importante mencionar que todas as larvas, neste estudo, estavam restritas às serosas das vísceras e serosas abdominais, o que pode indicar a necessidade de estudos mais específicos que, para diferentes espécies de peixes, podem resultar em protocolos diferentes de congelamento. Knoff et al (2007) salientaram que o meio mais eficaz para o controle da anisaquíase humana é a proibição da venda de peixes que não sejam submetidos aos processos descritos acima, frisando a importância da evisceração dos peixes imediatamente após Tabela 1. Prevalência (P), abundância média (AM), intensidade média (IM) e local de infecção das larvas de anisaquídeos encontradas na musculatura somática de Pagrus pagrus do litoral do Estado do Rio de Janeiro.…”
Section: Introductionunclassified